Student Financial Management Behavior: Factors Potential - Santus, Antonius; Erawati, Teguh (International Journal of Economics Development Research (IJEDR), 2024)
Financial behavior is an individual's ability to manage (planning, budgeting, checking, managing, controlling, disbursing, and storing) daily finances is one of the most talked about. This research focuses on "Student Financial Management Behavior: This study aims to determine the effect of lifestyle variables and self-awareness on student financial management behavior at Sarjanawiyata Tamansiswa University in Yogyakarta. This research is quantitative and conducted using survey method.  Primary data in this study were obtained through Google Forms and 100 respondents with convenience sampling technique. The technique used to test the proposed model is multiple linear regression analysis and processed using SPSS 25. The results show the direct influence of lifestyle and self-awareness on the financial management behavior of students at sarjanawiyata tamansiswa university. The lifestyle of students is very varied so that financial management behavior also varies depending on their perception of control over financial decisions while low self-awareness requires special attention from parents to improve student financial management.